Altered gut microbiota in Rett syndrome. Issue 1 (December 2016) - Strati, Francesco; Cavalieri, Duccio; Albanese, Davide; De Felice, Claudio; Donati, Claudio; Hayek, Joussef; Jousson, Olivier; Leoncini, Silvia; Pindo, Massimo; Renzi, Daniela; Rizzetto, Lisa; Stefanini, Irene; et al.
Abstract Background The human gut microbiota directly affects human health, and its alteration can lead to gastrointestinal abnormalities and inflammation. Rett syndrome (RTT), a progressive neurological disorder mainly caused by mutations inMeCP2 gene, is commonly associated with gastrointestinal dysfunctions and constipation, suggesting a link between RTT's gastrointestinal abnormalities and the gut microbiota. The aim of this study was to evaluate the bacterial and fungal gut microbiota in a cohort of RTT subjects integrating clinical, metabolomics and metagenomics data to understand if changes in the gut microbiota of RTT subjects could be associated with gastrointestinal abnormalities and inflammatory status. Results Our findings revealed the occurrence of an intestinal sub-inflammatory status in RTT subjects as measured by the elevated values of faecal calprotectin and erythrocyte sedimentation rate. We showed that, overall, RTT subjects harbour bacterial and fungal microbiota altered in terms of relative abundances from those of healthy controls, with a reduced microbial richness and dominated by microbial taxa belonging toBifidobacterium, several Clostridia (among whichAnaerostipes, Clostridium XIVa, Clostridium XIVb ) as well asErysipelotrichaceae, Actinomyces, Lactobacillus, Enterococcus, Eggerthella, Escherichia/Shigella and the fungal genusCandida . We further observed that alterations of the gut microbiota do not depend on the constipation status of RTT subjects and that this dysbiotic microbiota produced altered short chain fatty acids profiles. Conclusions We demonstrated for the first time that RTT is associated with a dysbiosis of both the bacterial and fungal component of the gut microbiota, suggesting that impairments of MeCP2 functioning favour the establishment of a microbial community adapted to the costive gastrointestinal niche of RTT subjects. The altered production of short chain fatty acids associated with this microbiota might reinforce the constipation status of RTT subjects and contribute to RTT gastrointestinal physiopathology.